Implementación del sistema de gestión en seguridad y salud en el trabajo en la empresa Luvicor Ingeniería S.A.S. de acuerdo con el decreto 1072 del 26 de mayo de 2015 (2017)
The main objective of this degree work is to implement an Occupational Health and Safety Management System (OHSMS) at the company Luvicor Ingeniería S.A.S. according with Decree 1072 of 2015 "Single Decree of Work", in order to improve working conditions in the company, mitigating accidents and work incidents with safe and beneficial work spaces for each of the workers according to the activities that are making.